GAMBARAN TINGKAT PENGETAHUAN DAN PERILAKU MASYARAKAT TERHADAP SWAMEDIKASI PENYAKIT GASTRITIS DI DESA GAGAAN KABUPATEN BLORA - Febyana Dewi Shinta; Paulina Maya Octasari (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Self-medication is an effort to treat the common health problems or symptoms without medical supervision. Although it has good intentions, self-medication also has the potential to be harm if it is not supported by adequate knowledge. The purpose of this study was to determine the level of community knowledge and attitude towards self-medication of gastritis in Gagaan Village, Blora Regency. This cross-sectional study was undertaken in Gagaan, Blora, Central Java, Indonesia. The study population consisted of people who had done self-medication about gastritis. The respondents were briefed about the nature of the study and the way to answer the pre-validated questionnaire. The type of questionnaire was closed ended questions for knowledge level assessment and likert scale questions for attitude level assessment. The data was analysed and were espressed as percentage. The questionnaire was administered to 113 respondents who had self-medicated for gastritis. Out of the 113 respondents, 64 (56,6%) were female and 49 (43,4%) were male; their mean age in years + SD was 33,15. + 13,94; 75 (66,4%) were worker; and 48 (42,5%) were undergraduate. Of the respondents, 92,9% had a high level of knowledge and 76,1% had a good attitude in the self-medication of gastritis. More than 70% (72,1%) respondents had a high knowledge level and good attitude. Knowledge of appropriate self-medication was high and attitude towards self-medication was good.